Analysis of the Implementation of the Merah Putih Village Cooperative from a Political Economy Perspective - Aminullah (CV. Satria Jaya, 2025)
This study aims to analyze the implementation of the Merah Putih Village Cooperative (Koperasi Desa Merah Putih) program from a political economy perspective, focusing on policy motivations, institutional challenges, and its impact on village economic governance. Employing a qualitative methodology, the research is grounded in a comprehensive literature review and policy document analysis, encompassing official government sources and academic studies. The findings indicate that while the Merah Putih Village Cooperative initiative holds potential for enhancing food security and empowering local economies, its implementation encounters significant challenges. These challenges include a top-down approach that may overlook local contexts, potential politicization of the program, and limited human resource capacity at the village level. Additionally, concerns arise regarding the possible overlap with existing Village-Owned Enterprises (BUMDes) and the risk of misusing village funds. The study concludes that a more participatory and context-sensitive approach is essential for the successful implementation of the Merah Putih Village Cooperative program. Strengthening institutional capacity, ensuring transparency in fund management, and fostering synergy between central and village governments are crucial for the program's success and sustainability.